Service quality of Lagro High School Library from the viewpoint of its hearing-impaired clients - Mateo, Rosa Marikit M.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
Service quality, that used to apply only to commercial establishment, has now reached the halls of academic institution's most important facility - the library. As a concept, it has become synonymous with such terms as satisfaction survey. The measurement of service quality has evolved into a method called the SERVQUAL model. The model is based on gap analysis, that is, the gap between expectations and performance, showing how customers rate the service quality in the library. The SERVQUAL has been further developed to apply to customers with disabilities.
This study attempts to show how the results of data collection using the SERVQUAL survey questionnaire can be used in the planning and determining of priorities for the delivery of library services for the hearing impaired. This group of people has special needs and expectations that need to be considered in the development and improvement of library services.
Using the Lagro High School and its library services for its hearing-impaired population, this study hopes to find out the applicability of the SERVQUAL data collection instrument in a Philippine public high school; to shed light on the quality of library services a public high school gives to its hearing - impaired population, and to suggest recommendations to improve the quality of its library service for the hearing - impaired students, including learning resources / collection, services and programs.
A total of 60 hearing - impaired students served as respondents of this study. The questionnaire used for this study was adopted from the studies of Hernon and Calvert (2006) with modifications done to fit the situations found in the Lagro High School. The questionnaire includes 28 statements to be rated in a Likert scale for expectations and actual performance of service, nine dimensions pertaining to library features and questions on respondent's characteristics. The measures of central tendency were used for data analysis and interpretation.
The results of the gap analysis point to problems in the aspects of provision (mainly the lack) of assistive technologies for the hearing-impaired students and the ability of the staff in rendering library services. With the SERVQUAL instrument, the students were able to point out aspects of library service that are being provided by their library, in particular, services that need to be reviewed and to be acted upon immediately, and services that require more long-term strategic planning. Knowledge of the service expectations and information needs of the hearing-impaired is essential for the continuous improvement of library services.
It is recommended that Lagro High School should focus and do more research to assistive technologies that can be installed in the school library for the use of their hearing-impaired students.
More research studies on disabilities should also be conducted to continuously find ways to recognize and be familiar with the information needs of the hearing-impaired. Also enumerated in this study are the learning resources / collections, services and programs suited to the information needs of the hearing-impaired students.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Lagro High School Library; Libraries and the hearing impaired -- Philippines -- Quezon City; School libraries -- Services to people with disabilities -- Philippines -- Quezon City